On the effect of aromatherapy with citrus fragrance in the therapy of major depressive disorder - Pereira, Maria Alice Ornellas [UNESP]; Pereira Jr., Alfredo [UNESP] (OMICS International, 2014)
The effect of aromatherapy on the human central nervous system is a controversial issue in medical sciences. Here we present a hypothesis relating citrus fragrance aromatherapy with brain glucose homeostasis in Major Depressive Disorder. How to conciliate the correlation between depression and resistance to insulin with the fact that glucose transport to neurons is not made directly by insulin? We briefly discuss the mechanism of dynamical glucose balance in the brain, which includes lactate transport from astrocytes to neuronal mitochondria supporting ATP (and then cAMP) production. We hypothesize that odors like vanillin and citrus fragrances fool the brain’s glucose level sensors, reducing the subjective feeling of "low energy". This hypothesis can help to explain the surprisingly positive results found in the treatment of depression with aromatherapy.
Keywords: Depression; Glucose; Lactate; Brain homeostasis; Reward system; Aromatherapy